PERAN ORIENTASI KEWIRAUSAHAAN MEMEDIASI PENGARUH DUKUNGAN PEMERINTAH TERHADAP KEUNGGULAN BERSAING BERKELANJUTAN UKM - Yani, Ni Wayan Merry Nirmala; Widya Hadi Saputra, I Gusti Ngurah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023, 2023)
SMEs are one of the important pillars in efforts to improve the national economy. SMEs are able to increase the wheels of the national economy because SMEs are able to absorb labor to reduce unemployment. The problems that are often faced by SMES are not being able to compete in the era of globalization due to the lack of a sustainable competitive advantage caused by the lack of support from government agencies (financial support or non-financial support) and the lack of entrepreneurial orientation of SMES business practitioners. The purpose of this study is to determine the effect of government institutional support on the sustainable competitive advantage of SMEs in Denpasar and explore the role of entrepreneurial orientation in mediating the relationship between government institutional support and sustainable competitive advantage. The sample in this study is 100 SMES in Denpasar, analyzed by using PLS (Partial Least Square) analysis technique. The results of this study found that: government institution support a significant positive effect on the sustainable competitive advantage and Entrepreneurial Orientation. Entrepreneurial orientation also has a significant positive effect on the Sustainable Competitive Advantage. Finally, entrepreneurial orientation has a partial mediation effect between government institution support Sustainable Competitive Advantage.